Digital Gamification as a Policy Instrument for Safeguarding Gorontalo’s Oral Traditions - Yurifto Sastro; Asna Aneta; Muchtar Ahmad (Lembaga Riset Ilmiah, 2026)
Gorontalo’s oral traditions, as part of its intangible cultural heritage, face serious threats due to the declining use of the local language, changes in the communication patterns of the younger generation, and the dominance of digital technology, which is displacing conventional mechanisms of cultural transmission. Various preservation efforts undertaken to date have tended to be documentary in nature and have not yet been able to sustainably increase the involvement of the younger generation. This study aims to develop a digital gamification model as a policy instrument to support the preservation of Gorontalo’s oral traditions among the younger generation. The research employs a qualitative approach using the Design Science Research (DSR) method, which encompasses problem identification, formulation of solution objectives, design and development of artifacts, demonstration, evaluation, and communication of results. Data were collected through observation, in-depth interviews, Focus Group Discussions (FGDs), and documentation involving 26 informants comprising elementary school students, teachers, school principals, cultural figures, academics, and local government officials. The artifact evaluation was conducted by six validators representing the fields of culture, language, educational technology, gamification, and public policy. The research findings indicate that limited proficiency in the Gorontalo language, the perception of oral traditions as an outdated culture, and limited exposure to local culture in the digital environment are the primary factors contributing to the declining interest of the younger generation in Gorontalo’s oral traditions. As a solution, this study developed a digital gamification model that integrates elements such as points, badges, levels, leaderboards, and narrative-based learning into Gorontalo oral tradition content. The developed model enhances user engagement through a more interactive, contextual, and generation-appropriate learning experience. The primary contribution of this study lies in the development of digital gamification positioned not only as a learning medium but also as an innovative policy instrument in the governance of intangible cultural heritage preservation at the regional level. These findings expand the study of public policy innovation by demonstrating the potential of gamification technology as a new mechanism to support the sustainability of oral traditions in the digital age.